2021
DOI: 10.1111/tpj.15261
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry‐based quantification and spatial localization of small organic acid exudates in plant roots under phosphorus deficiency and aluminum toxicity

Abstract: Low-molecular-weight organic acid (OA) extrusion by plant roots is critical for plant nutrition, tolerance to cations toxicity, and plant-microbe interactions. Therefore, methodologies for the rapid and precise quantification of OAs are necessary to be incorporated in the analysis of roots and their exudates. The spatial location of root exudates is also important to understand the molecular mechanisms directing OA production and release into the rhizosphere. Here, we report the development of two complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 89 publications
3
12
0
Order By: Relevance
“…This level of increased dynamics suggests higher levels of plant-secreted carbon compounds in the root cap attracting bacteria and encouraging replication. Such a possibility is consistent with reports of higher production of arabinogalactan-proteins and certain organic acids at root tips 38 , 39 , which can serve as carbon and energy sources for the bacteria. Phasor plots from the colonized roots can be seen in Supplemental Section S3 .…”
Section: Resultssupporting
confidence: 91%
“…This level of increased dynamics suggests higher levels of plant-secreted carbon compounds in the root cap attracting bacteria and encouraging replication. Such a possibility is consistent with reports of higher production of arabinogalactan-proteins and certain organic acids at root tips 38 , 39 , which can serve as carbon and energy sources for the bacteria. Phasor plots from the colonized roots can be seen in Supplemental Section S3 .…”
Section: Resultssupporting
confidence: 91%
“…Stress‐induced changes in metabolite localization is not exclusive to lipids. Arabidopsis roots under altered phosphate conditions showed differences in the exudation of organic acids citrate and malate (Gomez‐Zepeda et al ., 2021). Finally, a comparative MSI (and NMR) study showed different drought‐tolerance strategies utilized within roots of three tropical plant species ( Piper sp., Hibiscus rosa sinensis , Clitoria fairchildiana ), with heterogeneous spatial patterns in a range of metabolites associated with structural, redox, and microbial defense (Honeker et al ., 2022).…”
Section: Mass Spectrometry Imaging – a Chemical Imaging Platformmentioning
confidence: 99%
“…However, further optimization in sample preparation is indispensable for better spectral quality ( Dias et al., 2016 ). Further, MSI-based techniques were utilized to directly depict the spatial distribution of metabolites in the rhizosphere of Zea mays L. plants, Brachypodium distachyon roots, Arabidopsis seedlings, Asparagus roots, tomato roots and Marchantia polymorpha gemmalings ( Sasse et al, 2020 ; Korenblum et al., 2020 ; Döll et al., 2021 ; Gomez-Zepeda et al., 2021 ; Lohse et al., 2021 ). Additionally, LSC-MS allows for the detection of hundreds of plant-specific metabolites acquired from a single plant cell, discriminating them from those produced by soil microbes ( Masuda et al., 2018 ; Taylor et al., 2021 ).…”
Section: Analytical Methods For Metabolite Profiling Of Root Exudatesmentioning
confidence: 99%